An object oriented approach to multidimensional semiconductor device simulation - Müller, Stephan (Hartung-Gorre, 1994)
"This thesis presents a way to overcome the serious problems that have linited this in the past. The main emphasis is given to the object oriented design techniques employed in this approach"--Back cover.
Zugl.: Zürich, Eidgenössische Techn. Hochsch., Diss., 1994
Keywords: Object-oriented programming (Computer science); Semiconductors -- Computer simulation; Objektorientierte Programmierung; Mathematisches Modell; Halbleiterschaltung; Hochschulschrift